Evaluasi Ekstrak Bunga Asoka sebagai Indikator Alami Deteksi Boraks pada Sampel Makanan Olahan - Desy Purwaty; Sartika Magdalena Sihite; Ilham Pratama; Santa Ceacilia Br Tarigan; Stevani Putri Christie Gulo; Eka Setiawan; Larasati Arum Utami (Universitas Cokroaminoto Palopo, 2026)
Borax is a prohibited food additive but is still found in processed foods in Indonesia. This study aims to evaluate Saraca asoca leaf extract as a natural indicator for borax detection. The extract was prepared using 70% ethanol and tested on borax solutions and food samples. The results showed a color change from brownish-green to yellow with increasing borax concentration, starting at 1.0%. Similar changes in several samples indicated the presence of borax. This change is related to interactions between flavonoid and tannin compounds and borate ions. Therefore, Saraca asoca extract has potential as a simple natural indicator for visual borax detection